Penerapan Extreme Programming (XP) Sistem Inventory Kontrol Pada Gudang Hizam Sandal - Masripah, Ulpah; Setiawan, Ridwan (Institut Teknologi Garut, 2025)
In the midst of rapid technological development, manual recording in inventory management in the sandal trading industry often leads to errors, inefficiency, and accumulation of goods. This research aims to develop a web-based inventory control system using the First In First Out (FIFO) algorithm with the Extreme Programming (XP) approach, one of the agile software development methods that emphasizes collaboration, rapid iteration, and continuous testing. System development includes modeling with Use Case Diagram, Class Diagram, and designing with CRC Card. The final result in the form of an inventory system for Hizam Sandal Warehouse was tested using black-box testing and acceptance testing methods based on User Stories, which showed that the system runs as needed. The implementation of this system succeeded in increasing the efficiency of recording, reducing data errors, and facilitating the analysis of the accumulation of goods.